¿Eficiencia ferroviaria o interés social? Especulaciones sobre aspectos territoriales del polémico Plan Larkin. Argentina, 1962 - Saus, María Alejandra (2016)
Criticized by railway trade unionists for considering the project of reducing employment with rationalizing purposes, accused of being responsible for presumed fraudulent interests incarnated in the figure of its intellectual author and external financing sources, the Long Range Transportation Plan (1962) has had always a suspicious reputation. It consisted of exhaustive studies which tackled Argentinian transportation in a comprehensive way and, at the same time, it was also the target of a solid syndicalist resistance. Based on the original publication, a technical document full of statistical tables and concept maps, this article will review its contents in a dispassionate form and it will appreciate, with certain degree of justice, its historical contribution to the study of the Argentinian railway web and its relationship with the organization of its geographical space.